2022
DOI: 10.3390/dj10050083
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance Comparing Titanium and Titanium–Zirconium or Zirconia Dental Implants: A Systematic Review of Randomized Controlled Trials

Abstract: Objectives: This study aimed to compare clinical results between titanium (Ti), zirconia (Zr), or titanium–zirconium (TZ) dental implants and to analyze survival rate (SR), bleeding on probing (BoP), marginal bone loss (MBL), and/or probing depth (PD). Data source: Manual and electronic searches were conducted (PubMed and Web of Science) to identify randomized controlled trials that compared the outcomes of at least two implant types (control and test group) within the same study. The focused question was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Furthermore, this review may be the first to reveal that the PPD of Ti and Zr implants is comparable and significant under normal and experimental mucositis conditions, respectively. A recent systematic review failed to draw a definitive conclusion owing to the limitation in sample sizes of the included studies ( Fernandes et al, 2022 ). Under healthy conditions, a study revealed that the PPD was significantly greater around Ti implants than around teeth in the same patient (mean PPD difference = 0.8 mm, SD = 0.1 mm, P < 0.001) after 3-year follow-up ( Johnson & Persson, 2000 ), whereas the PPD around the Zr implants statistically significantly lower than around the control teeth at a 3-year follow-up time ( r = 0.56, P < 0.003) was observed in another trial ( Brüll, Van Winkelhoff & Cune, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this review may be the first to reveal that the PPD of Ti and Zr implants is comparable and significant under normal and experimental mucositis conditions, respectively. A recent systematic review failed to draw a definitive conclusion owing to the limitation in sample sizes of the included studies ( Fernandes et al, 2022 ). Under healthy conditions, a study revealed that the PPD was significantly greater around Ti implants than around teeth in the same patient (mean PPD difference = 0.8 mm, SD = 0.1 mm, P < 0.001) after 3-year follow-up ( Johnson & Persson, 2000 ), whereas the PPD around the Zr implants statistically significantly lower than around the control teeth at a 3-year follow-up time ( r = 0.56, P < 0.003) was observed in another trial ( Brüll, Van Winkelhoff & Cune, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis conducted in 2017 did not evaluate Zr and Ti implants in randomized controlled trials (RCTs) with a comparable baseline and has been outdated ( Elnayef et al, 2017 ). Furthermore, a recent systematic review did not quantitively analyze the differences between Zr and Ti implants ( Fernandes et al, 2022 ). As such, a novel systematic review and meta-analysis of RCTs is necessary to provide up-to-date evidence-based recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Dental implants remain the ideal treatment option for supporting prosthetic restorations in patients with partial and/or complete edentulism [ 1 ]. Unfortunately, in the atrophic edentulous maxilla, poor bone quantity and quality may inhibit the use of conventional dental implants [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, studies have been carried out to find the most suitable material for the composition of the implants and the consequent success or failure of their osseointegration [3][4][5]. The most scientifically studied implants are titanium implants, and more recently, investigations and comparisons with zirconia material have emerged [3][4][5]. According to Hanawa (2020) [6], titanium has shown excellent biocompatibility, corrosion-resistance, and high fracture toughness based on high strength and elongation.…”
Section: Introductionmentioning
confidence: 99%